A Consideration of Gradeless Learning in Higher Education - Adan Amer; Gaganpreet Sidhu; Seshasai Srinivasan (International Journal of Pedagogy and Teacher Education, 2023)
This article presents a brief overview of the purpose, implementation, and criticisms of the typical graded system 'used by most schools worldwide to assess students' academic performance. Letter and numerical grades serve many purposes, such as motivating students and allowing teachers or parents to track progress, yet this tool is quite unreliable for measuring knowledge acquisition. The overuse of grades to measure student success also impedes intrinsic learning outcomes, such as discovering interests or developing skills essential for transforming post-secondary students into lifelong learners. In contrast, gradeless learning systems that emphasize the application of knowledge and high-quality feedback can improve 'students' well-being and overall learning outcomes. Despite these benefits, switching away from grades is a tumultuous one given that students rely on them for motivation to perform well in school. Hopefully, implementing gradeless learning on a program or course level will be the first step in achieving this paradigm shift.